Empowerment Construction Management of Processed Porang (Amorphophallus Muelleri) through Responsible Consumption and Production Approach to Accelerate Food Sustainability on Marginal Land in East Java - Wahyudi, Suhud; Soehardjoepri,; Hari, Yulius; Widiana, Muslichah Erma (Migration Letters, 2024)
Indonesia have a vast farmland but only 58.4% be used for agriculture. It should support national food security afterwards. The porang plant (amorphophallus muelleri) is an economically valuable alternative food. According to data from East Java Surabaya Agricultural Quarantine Center (BBKP) porang exports grew from 2018 to 2020. The volume was 5,516,382 kg and Rp 270,302,720,450 in 2018. China, Vietnam, Japan, Thailand, Singapore, South Korea, and Taiwan exported. The volume was 6,064,947 kg and worth IDR 297,182,412,310 in 2019. Thailand, China, Taiwan, Vietnam, Cambodia, Pakistan are destinations. Porang is rarely used as an alternative food component in Indonesia. So that strategic efforts must be done to promote this development holistically from upstream to downstream to encourage economic growth for local residents, especially in suboptimal land regions. On the other hand, Ministry of PPN found that Indonesia lost 23-48 million tons of food between 2000–2019, or 115-184 kg per inhabitant. Food ingredients are extremely prone to waste. Indonesia generates the most Southeast Asian food waste. The Indonesian food waste is 20.93 million tons per year. Food waste costs Indonesia Rp 213-551 trillion per year, or 4-5% of its GDP Indonesia develops diversified and sustainable local food sources for food security. Porang is a notable food. The growth of porang in Madiun City can improve food security. Developing micro and medium agro-industrial firms is possible for Madiun residents. Madiun City porang farmers also benefit from the rising domestic and international porang market. This is crucial for climate change and global food price fluctuations-related food security. Porang development needs substantial help from Madiun municipal and relevant entities. With sustainable porang development, Madiun City can help achieve national food security. In addition to economic benefits and local food variety, porang can help Madiun and its neighbors access quality and sustainable food. This study develops a Responsible-Consumption-and-Production (RCAP) paradigm using processed porang to enhance food security on suboptimal land in East Java, Indonesia. Porang farmer samples and targets in Madiun, East Java.